Regulation of the Migration of Distinct Dendritic Cell Subsets - Feng, Meng; Zhou, Shuping; Yu, Yong; Su, Qinghong; Li, Xiaofan; Lin, Wei (Frontiers in Cell and Developmental Biology, 2021)
Dendritic cells (DCs), a class of antigen-presenting cells, are widely present in tissues and apparatuses of the body, and their ability to migrate is key for the initiation of immune activation and tolerogenic immune responses. The importance of DCs migration for their differentiation, phenotypic states, and immunologic functions has attracted widespread attention. In this review, we discussed and compared the chemokines, membrane molecules, and migration patterns of conventional DCs, plasmocytoid DCs, and recently proposed DC subgroups. We also review the promoters and inhibitors that affect DCs migration, including the hypoxia microenvironment, tumor microenvironment, inflammatory factors and pathogenic microorganisms. Further understanding of the migration mechanisms and regulatory factors of DC subgroups provides new insights for the treatment of diseases, such as infection, tumors, and vaccine preparation.